Investment, ZIS Funds, Mudharabah Financing and Economic Growth in Indonesia - Ichsan Hamidi; Muhammad Farhan; Deassy Apriani (Islamic Economics Journal, 2024)
This study conducted to investigate the effect of investment, ZIS funds, and mudharabah financing towards Indonesia's economic growth during the period 2011-2021. This study uses a quantitative approach with multiple linear regression analysis of monthly time series data. The results showed that investment realization has a positive and significant effect on economic growth, in accordance with Schumpeter's theory which highlights the role of investment in encouraging economic activity. Meanwhile, the distribution of ZIS funds has a positive but insignificant effect on economic growth with  0,7127 p-value, due to a lack of public trust in zakat amil institutions in Indonesia, That caused lack of ZIS funds to be distributed in encouraging economic growth. Mudharabah financing also has a positive but insignificant effect on economic growth with 0,5224 p-value, due to a small value of financing and low public interest in applying for mudharabah financing. It is hoped that the results of this study can become a basis for strengthening the role of Islamic economics, especially ZIS and mudharabah towards economic growth in Indonesia and improving people's welfare.